Manifestation of GIS tools for spatial pattern distribution analysis of dengue fever epidemic in the city of Subang Jaya, Malaysia - Che Dom, Nazri; Abd Latif, Zulkiflee; Ahmad, Abu Hassan; Ismail, Rodziah; Pradhan, Biswajeet (Thai Society of Higher Education Institutes on Environment, 2012)
Dengue has now emerged as one of the major public health problems in Malaysia. It was first reported in 1901 in Penang and since then the disease has become endemic concentrating mostly in urban areas. This study used the temporal-spatial model to determine high risk areas for dengue outbreak by measuring three temporal risk characteristics (i.e. frequency, duration and intensity) in order to define the severity and magnitude of outbreak transmission. This study examined a total of 4,651 confirmed dengue fever cases, geo-coded by address in the city of Subang Jaya between January 2006 and December 2009. The values of the three indices were considered high in a spatial unit when their standard values were positive. Measurement of the three temporal risk indices found that there were areas with significant high value for each of the temporal indices. This suggested that areas within Subang Jaya Municipality had different temporal characteristics for dengue occurrence. The utilization of three risk measures enabled to identify higher-risk areas for the occurrence of dengue fever. Even though case notification data are subjected to bias, this information is available in the health services and can lead to important conclusions, recommendations and hypotheses. As a recommendation, the temporal risk indices can be utilized by public health officials to characterize dengue rather than relying on the traditional case incidence data.